2019
DOI: 10.1080/15548627.2019.1569912
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inhibition specifically promotes epithelial-mesenchymal transition and invasion in RAS-mutated cancer cells

Abstract: Macroautophagy/autophagy inhibition is a novel anticancer therapeutic strategy, especially for tumors driven by mutant RAS. Here, we demonstrate that autophagy inhibition in RAS-mutated cells induces epithelial-mesenchymal transition (EMT), which is associated with enhanced tumor invasion. This is at least partially achieved by triggering the NFKB/NF-κB pathway via SQSTM1/p62. Knockdown of ATG3 or ATG5 increases oncogenic RAS-induced expression of ZEB1 and SNAI2/Snail2, and activates NFKB activity. Depletion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 67 publications
(114 reference statements)
2
97
0
Order By: Relevance
“…(Macro) autophagy is where a double-membraned vesicle is formed, which captures material in the cytoplasm to be degraded, whereas selective autophagy specifically targets cargo to be degraded [12][13][14][15] . Autophagy has also been proposed to have roles in a number of diseases [16] , such as fibrosis [17][18][19] , neurodegeneration [20] and cancer [21,22] [ Figure 2].…”
Section: Autophagymentioning
confidence: 99%
See 2 more Smart Citations
“…(Macro) autophagy is where a double-membraned vesicle is formed, which captures material in the cytoplasm to be degraded, whereas selective autophagy specifically targets cargo to be degraded [12][13][14][15] . Autophagy has also been proposed to have roles in a number of diseases [16] , such as fibrosis [17][18][19] , neurodegeneration [20] and cancer [21,22] [ Figure 2].…”
Section: Autophagymentioning
confidence: 99%
“…Numerous studies in different contexts have demonstrated interactions between autophagy and EMT, although it does appear this is both context-and tissue-dependent [ Table 1]. Studies have shown that manipulation of autophagy can promote EMT, invasion and metastasis [21,27,[38][39][40] ; these have been demonstrated in a wide variety of tissues/cell lines including pancreatic, breast, colorectal, melanoma and gastric. In total, 1400 tumours from 20 different types of cancers were analysed for LC3B, an autophagy marker, and it was found that increased expression was associated with metastasis and invasion [27] .…”
Section: Emt and Autophagy: A Complex Relationship In Malignancymentioning
confidence: 99%
See 1 more Smart Citation
“…SNAI2 (also known as Slug), a member of Snail superfamily, is one of the transcription factors of epithelial mesenchymal transition (EMT) [32]. In recent years, it has been found that SNAI2 is abnormally expressed in various kinds of malignant tumors and plays an important role in tumor progress and prognosis [33][34][35]. To investigate the role of SNAI2 in IM cells, we examined its expression level in IM tissues and BA-induced IM cells.…”
Section: Discussionmentioning
confidence: 99%
“…xenografts [46] HCC cell lines and xenografts [47] Loss of ULK1 to suppress autophagy in the MDA-MB-231 breast cancer cell line during hypoxia [48] Starvation- [49,50], TGF-β2- [51], or DRAM1induced [52] autophagy in hepatic carcinoma cell lines RAS-mutated cancer cells [53] TGFβ1-or rapamycin-induced autophagy in non-small cell lung cancer cells [54] Glioblastoma cell lines [55] Rapamycin-induced autophagy in CRC cell lines [56] Ovarian cancer cell lines [57] Cisplatin-induced autophagy in nasopharyngeal carcinoma cells [ MMTV-PyMT mice with FIP200 −/− conditional KO in mammary epithelial cells [40] Immunoediting…”
Section: Gastric Cancer Cell Lines and Mousementioning
confidence: 99%